2014
DOI: 10.1155/2014/189384
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated with Increased Breast Cancer Risk: A Systematic Review with Meta-Analysis

Abstract: Background. Although individual metabolic risk factors are reported to be associated with breast cancer risk, controversy surrounds risk of breast cancer from metabolic syndrome (MS). We report the first systematic review and meta-analysis of the association between MS and breast cancer risk in all adult females. Methods. Studies were retrieved by searching four electronic reference databases [PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and ProQuest through June 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 109 publications
(143 reference statements)
8
58
0
1
Order By: Relevance
“…[18] Existing lifestyle risk factors and the metabolic syndrome (high blood glucose, high BP, abnormal cholesterol levels and excess fat around the waist) have been associated with increased breast cancer risk, especially in postmenopausal women. [19][20][21][22] Studies in LMICs have shown that the prevalence of the metabolic syndrome in breast cancer patients can be as high as 40%. [21] It has also been reported that about a third of women with breast cancer are likely to experience psychological distress.…”
Section: Researchmentioning
confidence: 99%
“…[18] Existing lifestyle risk factors and the metabolic syndrome (high blood glucose, high BP, abnormal cholesterol levels and excess fat around the waist) have been associated with increased breast cancer risk, especially in postmenopausal women. [19][20][21][22] Studies in LMICs have shown that the prevalence of the metabolic syndrome in breast cancer patients can be as high as 40%. [21] It has also been reported that about a third of women with breast cancer are likely to experience psychological distress.…”
Section: Researchmentioning
confidence: 99%
“…Metabolic disorders, such as obesity and insulin resistance, have been suggested to be involved in the pathogenesis and progression of breast cancer [4][5][6]. Metabolic syndrome (MetS), which indicates a cluster of metabolic abnormalities including abdominal adiposity, insulin resistance, hyperglycemia, hypertension, and dyslipidemia [7][8][9][10], has been considered to be a risk factor of a variety of cancers, including breast cancer in postmenopausal women [11,12]. In addition, MetS have been proposed as a prognostic factor in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologically, MetS is considered as a status of low-grade chronic inflammation [10], which may also be involved in the pathogenesis of tumor development [11]. Consistently, results of epidemiology studies suggested that presence of MetS may confer higher risks for the development of variety categories of cancers, such the colorectal cancer [12], pancreatic cancer [13], breast cancer [14], endometrial cancer [15], hepatocellular carcinoma [16], and prostate cancer [17]. However, the association between MetS and the incidence of lung cancer, the most common malignant tumor of the world [18], has not been fully determined.…”
Section: Introductionmentioning
confidence: 88%